Prevalence of peripheral artery disease in diabetic patients of a tertiary care hospital - Meena, Sangeetha; C., Manikandan R. (International Journal of Advances in Medicine, 2019)
Background: Peripheral Arterial disease (PAD) is a major microvascular complication of diabetic mellitus. Patients with diabetes have an increased prevalence of PAD. The Ankle branchial Index (ABI) is an easy, noninvasive and often underutilized tool for diagnosis of PAD. The aim of this study is to detect the prevalence of PAD in diabetic patients using Ankle Brachial Index (ABI). Since most of the patients with PAD are asymptomatic, routine screening for the same is necessary to avoid lower limb ulcerations and amputation. Methods: In this cross-sectional study, 200 diabetic patients attending a tertiary care hospital in the Kancheepuram district of Tamilnadu were screened for the prevalence of PAD using ABI and to find out risk factors associated with it. Results: Among the 200 diabetic patients who underwent ABI measurements using handheld Doppler, 19.5% were found to be having PAD. Most of them were symptomatic. Age more than 50 years and female gender were considered as statistically significant (P<0.05) determinants of PAD. Conclusions: PAD is relatively common in elderly diabetics. ABI measurement is a valid tool in early detection of PAD and therefore regular follow up will decrease disabilities in the diabetic population.